Integrasi Wakaf dan Investasi Dana Haji menurut Hukum Positif dan Hukum Islam - Siska Lis Sulistiani; Udin Saripudin; Intan Nurrachmi (ITB AAS INDONESIA Surakarta, 2023)
This study aims to analyze the integration between waqf and hajj fund investment according to positive law and Islamic law. Waqf is an Islamic financial instrument that has social value and can be integrated with other Islamic financial instruments. Hajj fund investment is one of the financial instruments that should be used for the benefit of the people so that for individuals who intend to make pilgrimages their funds can be maintained and maintained and can provide other benefits as long as the funds are stored. This research is qualitative research with a normative juridical research method approach by using types and sources of legal data including, primary legal sources, namely Law no. 41 of 2004 concerning Waqf, Law No. 34 of 2014 concerning the financial management of Hajj and other regulations, the Al-Quran and Al-hadith. The results of this study are that the integration of waqf and Hajj financial investment can be carried out in collaboration to achieve greater benefits for the development of waqf in Indonesia.